2006
DOI: 10.1007/s10493-006-0006-2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Age of Field-collected Female Taiga Ticks, Ixodes persulcatus (Acari: Ixodidae), and their Infection with Borrelia burgdorferi Sensu Lato

Abstract: In some studies the prevalence of tick infection (infection rate) and the intensity of infection are negatively correlated with unfed tick age (in the broad sense of this term). However, no special research has been carried out to consider the phenomenon thoroughly. The infection indices of the female taiga ticks, Ixodes persulcatus, infected with Borrelia burgdorferi s.l. were related to tick physiological age, an index that more precisely reflects tick physiological state than the time of tick collection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Of epidemiological importance is the increase in activity and host-seeking behaviour observed in our starved ticks. Ticks can maintain pathogen infections through extended starvation (Uspensky, Kovalevskii, & Korenberg, 2006), are potentially more likely to encounter a host (this study) and take larger bloodmeals upon finding a host (Amin, 1969). Therefore, starved ticks may have an enhanced role as vectors of disease by composing a greater proportion of the questing population than ticks that have more recently fed.…”
Section: Discussionmentioning
confidence: 89%
“…Of epidemiological importance is the increase in activity and host-seeking behaviour observed in our starved ticks. Ticks can maintain pathogen infections through extended starvation (Uspensky, Kovalevskii, & Korenberg, 2006), are potentially more likely to encounter a host (this study) and take larger bloodmeals upon finding a host (Amin, 1969). Therefore, starved ticks may have an enhanced role as vectors of disease by composing a greater proportion of the questing population than ticks that have more recently fed.…”
Section: Discussionmentioning
confidence: 89%
“…It also was observed that infection by B. burgdorferi s.l. increased questing activity in Ixodes persulcatus Schulze (Naumov 1999 cited by Uspensky et al 2006) and host-Þnding efÞcacy in adult I. ricinus (Faulde and Robbins 2008).…”
mentioning
confidence: 99%
“…was recorded compared with the previous and following years (L.G., unpublished data). In addition, Naumov (2003) (cited by Uspensky et al 2006) noted that there was a trend toward an increase in the longevity of adult I. ricinus and I. persulcatus infected by B. burgdorferi s.l. spirochetes.…”
mentioning
confidence: 99%
“…It is the manner of determining if a tick is "young" (probably newly molted) or if it has already spent a long time questing in the vegetation, thus depleting energy resources [9]. The classic method is to measure the fat contents of the tick as a proxy of its energy reserves [2,9,10]. This is an effective but time-consuming procedure.…”
Section: The Evaluation Of the Physiological Stage Of A Tickmentioning
confidence: 99%